The Impact of Supply Chain Management on Organizational Performance: A Field Study in the Food Manufacturing Companies of Hael Saeed Anam Group and Partners - Majed Kassem Abdu Al-Sayani; Mohammed Qaid Ghanem (University of Science and Technology, Sana’a, Yemen, 2025)
The study aimed to identify the impact of supply chain management on organizational performance in the food manufacturing companies of Hail Saeed Anam Group and Partners. The study population consisted of employees in top, middle, and executive management who form the team dealing with supply chains, totaling 127 individuals. The study relied on a comprehensive census and adopted a descriptive-analytical approach, using a questionnaire as the data collection tool. Data were statistically analyzed using the Statistical Package for the Social Sciences (SPSS). The study revealed several key findings, the most important of which was the presence of a statistically significant positive impact of supply chain management on organizational performance in the food manufacturing companies of Hail Saeed Anam Group and Partners. The findings also showed that the companies achieved a high level of organizational performance in its two dimensions (efficiency and effectiveness), reflecting the success of supply chain management. The study provided several recommendations, including the importance of adopting sustainable strategies to improve organizational performance across its various dimensions, with a focus on enhancing efficiency and effectiveness through the implementation of modern systems that ensure accuracy and speed in task completion. Additionally, the study recommends strengthening collaboration with suppliers in research and development to increase innovation and achieve a higher level of integration, as well as building long-term relationships with customers and developing direct and effective communication channels with them, given their vital role in improving and advancing organizational performance.